Prostate Cancer UK: the Blue Skies Forum. Issue 6 (November 2013) - Kirby, Roger; Eeles, Ros; Neal, David; Ahmed, Hashim U.; Dearnaley, David
Abstract The second meeting of the Blue Skies Forum took place in Downing College, Cambridge, in April 2013, with the objective of focusing attention on new initiatives in the diagnosis and treatment of prostate cancer, in particular on areas of research that aim to identify aggressive disease. The meeting was hosted by Prostate Cancer UK and supported by The Howard Foundation. Copyright © 2013 John Wiley & Sons